Adolescence, sexuality, and the criminal law: multidisciplinary perspectives - Graupner, Helmut; Bullough, Vern L. (Routledge, Taylor & Francis Group, 2012)
Introduction / Helmut Graupner, Vern L. Bullough -- The 17-year-old child : an absurdity of the late 20th century / Helmut Graupner -- Age of consent : a historical overview / Vern L. Bullough -- Adolescent American sex / David Weiss, Vern L. Bullough -- An empirical examination of sexual relations between adolescents and adults : they differ from those between children and adults and should be treated separately / Bruce Rind -- 14 to 18 year olds as "children" by law? Reflections on developments in national and European law / Lilian Hofmeister -- Sexuality, adolescence and the criminal law : the perspective of criminology / Michael C. Baurmann -- Adolescence, sexual aggression and the criminal law / Lorenz Bllinger -- Prostitution of young persons : a topic of social work and/or penal legislation / Thomas Moebius -- Sexual consent : the criminal law in Europe and outside of Europe / Helmut Graupner.